Numerical simulation study on pressure response and fluid loss mechanism of coal fracture network under particle temporary plugging - Qiushuang Sun; Jian Chen; Liwen Guo; Jiaxuan Han; Yizheng Wang; Xinda Yang; Yanlei Guo; Xiangming Hu; Yee-Chung Jin; Guanhua Ni (PLoS ONE, 2026)
To address the issue of fluid loss leading to pressure failure when applying temporary plugging fracturing technology from the oil industry to enhance gas recovery in coal mines, and considering the current low efficiency of CO 2 solidification and utilization, a new method is proposed to inject SC-CO 2 and hot alkali solution together into coal to produce solidified particles as temporary plugging agents for solidification and utilization of CO 2 and fracturing transformation of coal. At present, the mechanisms governing pressure increase during temporary plugging with solidified CO 2 particles, as well as the relationship between internal pore and fracture pressures after plugging and fluid loss rate, remain unclear. Based on CT images, a complex geometric model of interconnected pores and fractures of coal is constructed. The morphology of solidified CO 2 particles is obtained via microscopic scanning, and conducts numerical simulation research on fluid solid coupling. Clearly define the pressure and flow distribution inside the coal under different temporary plugging positions and injection conditions. Revealing the pressure and fluid loss law inside the coal after temporary plugging. The results show that when particles are temporary plugging at different positions, the average internal pressure in the coal ranges from 8.05 MPa to 12.03 MPa. The fluid loss rate varies from 0.037 cm 3 /s to 0.152 cm 3 /s. Establish equations for the relationship between injection pressure, fracture size, temporary plugging location, internal pressure, and fluid loss rate, with a fitting formula R 2 of 0.988. Furthermore, an experimental setup and methodology involving supercritical CO 2 and hot alkali liquor injection were designed to validate the accuracy of the numerical simulation results regarding pressure enhancement and fluid loss under solidified particle plugging. This study provides theoretical support for enhanced coalbed methane recovery and the development of integrated technologies for underground CO 2 storage and hydraulic control of gas emissions.